2003
DOI: 10.1002/cne.10895
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor corticocortical projections from rat barrel cortex have an anisotropic organization that facilitates integration of inputs from whiskers in the same row

Abstract: We used a dual anterograde-tracing paradigm to characterize the organization of corticocortical projections from primary somatosensory (SI) barrel cortex. In one group of rats, biotinylated dextran amine (BDA) and Fluoro-Ruby (FR) were injected into separate barrel columns that occupied the same row of barrel cortex; in the other group, the tracers were deposited into barrel columns residing in different rows. The labeled corticocortical terminals in the primary motor (MI) and secondary somatosensory (SII) cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
101
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 77 publications
22
101
0
Order By: Relevance
“…2B and 5B). The presence of a motor signal in S1 cortex is certainly consistent with the known topographic connections between vibrissa M1 and S1 cortices (Deschenes et al 1998;Hoffer et al 2003;Izraeli and Porter 1995;Keller et al 1996;Kim and Ebner 1999;Veinante and Deschenes 2003). However, it appears inconsistent with the findings of Fee et al (1997), in which spiking by S1 units in phase with the fast, cycle-by-cycle motion of the vibrissae was largely extinguished on a unilateral lidocaine block of transmission along the contralateral facial nerve.…”
Section: Signal Flow Between S1 and M1mentioning
confidence: 73%
See 1 more Smart Citation
“…2B and 5B). The presence of a motor signal in S1 cortex is certainly consistent with the known topographic connections between vibrissa M1 and S1 cortices (Deschenes et al 1998;Hoffer et al 2003;Izraeli and Porter 1995;Keller et al 1996;Kim and Ebner 1999;Veinante and Deschenes 2003). However, it appears inconsistent with the findings of Fee et al (1997), in which spiking by S1 units in phase with the fast, cycle-by-cycle motion of the vibrissae was largely extinguished on a unilateral lidocaine block of transmission along the contralateral facial nerve.…”
Section: Signal Flow Between S1 and M1mentioning
confidence: 73%
“…First, there are extensive intercortical projections from S1 to M1 cortices (Hoffer et al 2003;Izraeli and Porter 1995;Keller et al 1996;Kim and Ebner 1999). These maintain the topography of the vibrissa organization, with the majority of axons originating in layer 5 of S1 cortex and terminating in superficial layers of M1 cortex (Izraeli and Porter 1995).…”
Section: Introductionmentioning
confidence: 92%
“…VMC is the most intensely investigated vibrissal motor structure. Recent work clarified the localization [41,46], subdivisions [48], cytoarchitectonics [41], and connectivity of VMC [52][53][54][55]. Single-cell stimulation experiments in VMC allow for determining the cellular basis of cortical motor control with unprecedented precision [20].…”
Section: Resultsmentioning
confidence: 99%
“…A recent anatomical study [53] demonstrated that S1 inputs from vibrissa rows converge in VMC. VMC, in turn, projects selectively to septal columns of barrel cortex [54].…”
Section: Organization Of the Vibrissa Motor Cortexmentioning
confidence: 99%
“…Cortical barrels within the PMBSF receive one-to-one input from specific vibrissae on the contralateral face and provide the major somatosensory input for the rodent to navigate through its environment (Welker and Woolsey, 1974). Output from barrel columns project, in part, to motor cortex where it serves to modulate motor output (Hoffer et al, 2003). Barrel size depends on thalamocortical input and a smaller barrel field and barrels reported here likely reflect diminished cortical sensitivity and reduced sensory feedback to motor cortex.…”
Section: Postnatal Alcohol Exposure and Pmbsf Area And Barrel Patternmentioning
confidence: 76%